Successful management of peripapillary choroidal neovascular membrane secondary to idiopathic intracranial hypertension with intravitreal ranibizumab - Nitin Kumar; Basavraj Tigari; Mohit Dogra; Ramandeep Singh (Indian Journal of Ophthalmology, 2018)
Idiopathic intracranial hypertension (IIH) is a common cause of papilledema in young females and causes headache with transient visual loss. Severe visual loss occurs due to optic atrophy or peripapillary choroidal neovascular membrane (PCNVM). PCNVM in IIH has an incidence of 0.5% with a benign course in the majority of patients. Intravitreal Anti-vascular endothelial growth factor agents have anecdotally been used to manage these patients, with complete resolution reported in all cases after a single injection. Our case of IIH-associated PCNVM was treated with three injections of intravitreal ranibizumab with no recurrence at 6-month follow-up.